The astonishing color of after - Pan, Emily X. R. (New York : Little, Brown and Company, 2018)
"Leigh Chen Sanders is absolutely certain about one thing: when her mother died by suicide, she turned into a bird. Leigh, who is half Asian and half white, travels to Taiwan to meet her maternal grandparents for the first time. There, sh is determined to find her mother, the bird. In her search, she winds up chasing after ghosts, uncovering family secrets, and forging a new relationship with her grandparents. And as she grieves, she must try to reconcile the fact that on the same day she kissed her best friend and longtime secret crush, Axel, her mother was taking her own life."--
Young adult
Keywords: Suicide -- Fiction; Grief -- Fiction; Artists -- Fiction; Racially mixed people -- Fiction; Grandparents -- Fiction; Paranormal fiction; Americans -- Taiwan -- Fiction; Young adult fiction; Secrets -- Juvenile fiction; Suicide -- Juvenile fiction; Grief -- Juvenile fiction; Artists -- Juvenile fiction; Racially mixed people -- Juvenile fiction; Grandparents -- Juvenile fiction; Secrets -- Juvenile fiction; Supernatural -- Juvenile fiction; Americans -- Taiwan -- Juvenile fiction; Taiwan -- Fiction; Taiwan -- Fiction; Paranormal fiction